Philosophy of Education in Postmetaphysical Thinking - Kondrla, Peter; Maturkanič, Patrik; Taraj, Martin; Kurilenko, Viktoria (Journal of Education Culture and Society, 2022)
Aim. The aim of the article is to define the possibilities of education in the concept of postmetaphysical thinking. The definition takes into account the need to understand education as an open process of developing an authentic personality. The new understanding of education helps to orient the educational process in the family and school towards the person of the pupil and the development of his real possibilities.Concept. The article is built around a comparison of metaphysical and post-metaphysical thought. It describes the fundamental differences between both types of thinking, with a focus on the importance of others and openness in the interpretation of fundamental pedagogical categories. Attention is paid to the understanding of the pupil, the teacher, the process of education, and the goal of education. The pupil is interpreted as a person who has individual and original abilities. The process of education is understood as the development of the individual abilities of the pupil. The objective of education is determined on the basis of the pupil's abilities. The aim of upbringing is not predetermined. The openness of pedagogical practice necessitates the openness to continuous updating of educational and training methods.Results and conclusion. Creation of a basic framework for the innovation of pedagogical practices. The proposed framework views pedagogical success as a means of finding a sense of self, leaves room for alternative solutions, and emphasises the importance of students' individual abilities. It allows for pedagogy based on acceptance of otherness. Through the pedagogy thus interpreted, it creates a path for creative solutions to educational problems while developing not only the individual abilities of students but also their capacity for tolerance, which is a prerequisite for the functioning of a democratic society, through the pedagogy thus interpreted.Cognitive value. The article presents problems that arise when using classical pedagogy, i.e. pedagogy based on metaphysical thinking. The aim of classical pedagogy is the passive passing of knowledge and the production of graduates with the same abilities and knowledge. Pedagogy based on a postmetaphysical approach educates pupils whose value is based on human nature. Each pupil is accepted according to his individual abilities. He is an original and authentic human being.